2D-STRAIGHT LINE PATH FOLLOWING AND NUMERICAL SIMULATION - Zafer Öznalbant; Uğur Özdemir; Mehmet Ş. Kavsaoğlu (Havacılık ve Uzay Teknolojileri Dergisi, 2018)
In this paper, a two-dimensional-straight-line path following methodology for an unmanned aircraft is developed. With the developed algorithm, the unmanned aerial vehicle is made to converge to a predefined path, and then to follow a virtual target on the path. A variable virtual target location is defined to get a smooth maneuver motion. The location of the virtual target is changed according to the magnitude of the cross track error which is the distance between the path and the aircraft itself. After defining the equations required for the calculation of the desired heading, the applied closed controller is explained. A numerical simulation model is created for the solution of equations of motion to investigate the outputs of the path following algorithm. The results of the algorithm and simulation are evaluated.